Analysis of the Application of Storage Resource Pool Technology of Inner Mongolia Power based on the Background of Big Data - Yu, Zhang; Wei, Ao (International Journal of Electric Power and Energy Studies, 2024)
With the continuous deepening of the Inner Mongolia Power Company’s level of informatization and the continuous expansion of the scale of business and application system construction, the company will also enter the era of big data, and the amount of data will show an explosive growth trend. In order to solve the problems of massive data storage and data value mining faced by the enterprise during its development process, research on the application of storage resource pool technology has been conducted. Ultimately, the unified planning, allocation, and management of storage resources have been achieved, greatly improving the utilization efficiency of storage resources.